Rapid Capillary Tube Method for Detecting Penicillin Resistance in Staphylococcus aureus - Rosen, Ira G. (Appl Microbiol, 1972)
A simple, rapid capillary tube test to discriminate between penicillin-resistant and -sensitive Staphylococcus aureus is presented. This test detects penicillinase in noninduced primary isolates from blood-agar plates.